2017
DOI: 10.18781/r.mex.fit.1612-7
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad genética de Hemileia vastatrix de dos Zonas productoras de café en el Perú

Abstract: <p>Se analizó la diversidad genética del patógeno del café <em>Hemileia vastatrix</em>, a través de secuenciación de los espaciadores internos transcribibles del ADN ribosomal (ITS). El análisis se realizó en muestras de roya de 12 predios de dos zonas cafetaleras del Perú, Quillabamba (Cusco) y Villa Rica (Pasco). Se hallaron los índices de diversidad haplotípica y nucleotídica. Además, se determinaron las semejanzas entre las poblaciones analizadas por medio de una red de haplotipos. Del an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
1
0
2
Order By: Relevance
“…The findings derived from the phylogenetic analysis indicate that the six specimens of the H. vastatrix population exhibit a lack of structure, indicating a homogenous population with no discernible differentiation based on geographic origin. The undifferentiated H. vastatrix population could have evolved from the movement of spores between the two areas transported by people, seed, and/or infected plants [40]. These findings are consistent with those obtained in Brazil by Cabral et al [41], who found no evidence of H. vastatrix populations being structured based on origin, host, or physiological race.…”
Section: Discussionsupporting
confidence: 90%
“…The findings derived from the phylogenetic analysis indicate that the six specimens of the H. vastatrix population exhibit a lack of structure, indicating a homogenous population with no discernible differentiation based on geographic origin. The undifferentiated H. vastatrix population could have evolved from the movement of spores between the two areas transported by people, seed, and/or infected plants [40]. These findings are consistent with those obtained in Brazil by Cabral et al [41], who found no evidence of H. vastatrix populations being structured based on origin, host, or physiological race.…”
Section: Discussionsupporting
confidence: 90%
“…H. vastatrix has considerable genetic variation, with more than 50 races that have been identified (Quispe‐Apaza et al., 2017). Races are distinguished by unique sets of virulence genes (Talhinhas et al., 2017; Zambolim, 2016).…”
Section: Why Were Outbreaks Of Clr So Severe In the Americas?mentioning
confidence: 99%
“…Finalmente, se ha encontrado en mayor cantidad especies de Hemileia vastatrix, en todas las zonas muestreadas, con baja incidencia de daño. No cabe duda que, H. vastatrix es patógeno con mayor ataque en plantas de café y además que posse una amplia variabilidad genetica (Malau, 2019;Quispe-Apaza et al, 2017;Talhinhas et al, 2017).…”
Section: Microconiosunclassified